Exploring vaginal microbiome: from traditional methods to metagenomic next-generation sequencing—a systematic review - Liu, Siying; Chen, Yuxin; Zhang, Kunxiu; Tang, Dan; Zhang, Ji; Wang, Yuxin; Zhao, Jiaqi; Li, Diyan; Wang, Tao (Frontiers in Microbiology, 2025)
Recent research has highlighted the vaginal microbiome as a crucial factor in women's health and fertility. The growing recognition of its significance has intensified the focus on studying the female reproductive tract's microbial ecosystem. While various analytical methods exist for examining the vaginal microbiome, metagenomic next-generation sequencing (mNGS) has emerged as an auspicious approach. This study examines how mNGS technology can be applied to analyze vaginal microbiota. We begin by exploring the relationship between vaginal bacterial communities and women's health, followed by a comparative analysis of metagenomics against other detection methods, highlighting their respective strengths and limitations. The paper systematically reviews different detection techniques, examining their fundamental principles, constraints, and advantages. Several factors can affect data quality, including sampling procedures, contamination issues, and PCR amplification errors. We suggest implementing third-generation sequencing (TGS) to address these challenges to enhance reproducibility and read length, utilizing single-molecule sequencing (SMS) to eliminate PCR amplification-related errors, and integrating multiple analytical approaches to provide comprehensive insights. In summary, mNGS technology allows us to collect valuable information at a lower cost, and it remains a leading method for detecting female reproductive tract microbes. The goal of this review is to describe the principle, benefits and drawbacks, and application areas of mNGS, as well as to serve as a reference for research into female reproductive tract microbial detection methods, promote the improvement of mNGS in the detection of female reproductive tract microbial technology, and ensure the health of the female reproductive tract.